O fortalecimento da identidade quilombola a partir do livro literário em uma turma multisseriada: um estudo de caso na E. M. Educador Paulo Freire, no quilombo Cruz da Menina - PB - Silva, Maria Liliane Santos da (2020)
Our study is part of the perspective of working with paradidactic books and quilombola schools in order to favor the adoption of values based on quilombola identity principles. We bring as locus of the research, the Municipal School Educator Paulo Freire, located in community of quilombola, Cruz da Menina, rural area of the municipality of Dona Inês- PB. We sought to analyze how the teacher works with the paradidactic books in the school to strengthen the quilombola identity. Above all, our research is consistent with what proposes Law No. 10,639/2003, for the guarantee of the teaching of African and Afro-Brazilian history and culture. We are based on the studies of Cavalleiro (2003, 2005); Gomes (2006, 2010); Zilberman (2003); Zilberman; Lajolo (2005) and Coelho (2000, 2010). In this direction, our research is qualitative of the single case study type, for this we rely on Robert Yin (2015) when we study a specific unit within a given context. We used for data collection and construction, the documentary analysis of the paradidactic books listed by the teacher of the said school as the most used to work the quilombola identity in his multiserial class from 2nd to 5th grade. These books are respectively: "Mama Panya's Pancakes" – Songs of the World Collection by Mary and Rich Chamberlin; "Song of the African Peoples" by Fernando Paixão; "Children: Look at Africa and see Brazil", by Pierre Verger and "My African grandfather" by Carmen Lúcia Campos. Similarly, a semi-structured interview was conducted with the teacher in charge of the class, based on Bauer and Gaskell (2015). We used content analysis Bardin (2011), Minayo (2016). In this context, we understand the importance of work from the paradidactic books of ethnic-racial themes to confront racism, however, it is necessary to look closely at the teacher (a) in the selection and didactic treatment of these works, not running the risk of passing through a still racist ideology.